Implementasi Analisis SWOT dengan Matriks IFAS & EFAS untuk Menentukan Strategi Pemasaran pada Mixue Rajamandala - Putri, Anggi Yulia; Wibowo, Indrajati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the appropriate marketing strategy for Mixue Rajamandala using a SWOT analysis, reinforced by the IFAS and EFAS Matrices, and then formulated into a TOWS Matrix. The background of this study is a decline in sales unrelated to local competition, but rather due to the suboptimal utilization of internal strengths and external opportunities. This study used a descriptive qualitative approach with a case study method, and data collection techniques through observation, documentation, and interviews. The analysis results showed a total IFAS score of 2.66 and an EFAS score of 2.68, placing Mixue Rajamandala in quadrant II of the TOWS Matrix (WO strategies). Recommended strategies include: increasing creative promotions through social media such as Instagram and TikTok, enhancing outlet comfort with aesthetic designs, collaborating with the local community, increasing store visibility through visual elements such as Mixue statues, and developing seasonal, non-ice cream products during the rainy season. The originality of this study lies in the finding that the decline in sales was not driven by competition, but rather by underutilized internal and external marketing strategies. This finding provides a new contribution to the study of marketing strategies, particularly in franchise businesses in semi-urban areas, which have so far tended to be underexplored in academic literature.